Exocyst subunit Exo70B2 is linked to immune signaling and autophagy. Issue 2 (3rd December 2020) - Brillada, Carla; Teh, Ooi-Kock; Ditengou, Franck Anicet; Lee, Chil-Woo; Klecker, Till; Saeed, Bushra; Furlan, Giulia; Zietz, Marco; Hause, Gerd; Eschen-Lippold, Lennart; Hoehenwarter, Wolfgang; Lee, Justin; et al.
Abstract: During the immune response, activation of the secretory pathway is key to mounting an effective response, while gauging its output is important to maintain cellular homeostasis. The Exo70 subunit of the exocyst functions as a spatiotemporal regulator by mediating numerous interactions with proteins and lipids. However, a molecular understanding of the exocyst regulation remains challenging. We show that, in Arabidopsis thaliana, Exo70B2 behaves as a bona fide exocyst subunit. Conversely, treatment with the salicylic acid (SA) defence hormone analog benzothiadiazole (BTH), or the immunogenic peptide flg22, induced Exo70B2 transport into the vacuole. We reveal that Exo70B2 interacts with AUTOPHAGY-RELATED PROTEIN 8 (ATG8) via two ATG8-interacting motives (AIMs) and its transport into the vacuole is dependent on autophagy. In line with its role in immunity, we discovered that Exo70B2 interacted with and was phosphorylated by the kinase MPK3. Mimicking phosphorylation had a dual impact on Exo70B2: first, by inhibiting localization at sites of active secretion, and second, it increased the interaction with ATG8. Phosphonull variants displayed higher effector-triggered immunity (ETI) and were hypersensitive to BTH, which induce secretion and autophagy. Our results suggest a molecular mechanism by which phosphorylation diverts Exo70B2 from the secretory into the autophagy pathway for its degradation, to dampen secretory activity. Abstract : Phosphorylation of Exo70B2 inhibits PM interaction and increases interaction with ATG8, diverting Exo70B2 into the vacuole by autophagy, linking signalling and autophagy to secretion. The author(s) responsible for distribution of materials integral to the findings presented in this article in accordance with the policy described in the Instructions for Authors (www.plantcell.org ) is: Marco Trujillo (marco.trujillo@biologie.uni-freiburg.de ).